Influence of Carbon Nanotubes on Enhancement of Sliding Wear Resistance of Plasma-Sprayed Yttria-Stabilised Zirconia Coatings - Chaithanya Kalangi; Venkateshwarlu Bolleddu (Advances in Materials Science and Engineering)
An experimental investigation was performed to study the performance of thermally sprayed yttria stabilised zirconia (YSZ) coatings obtained with the reinforcement of carbon nanotubes (CNTs) in different weight percentage proportions. The atmospheric plasma spray (APS) method was used to deposit YSZ + CNTs at three different weight proportions on low carbon steel (AISI 1020) following the industrial standard procedure. The quality of thermally sprayed coatings was evaluated to report on percentage porosity (ASTM B276), sliding wear resistance (ASTM G133-05), and metallurgical bonding of the coating with the substrate material. From this investigation results, it has been confirmed that the thickness of the coatings is almost uniform, and the percentage porosity is decreased with an increase in CNTs weight percentage proportion. ImageJ software has confirmed the presence of CNTs in the ceramic deposit, and also uniform distribution throughout the coating. Subsequently, the metallurgical bonding of the deposit is also ensured and confirmed that the deposit adheres on the substrate. The hardness of the coating found increased with the increase in CNTs proportion as 554 Hv with 1 wt.% CNTs, 805 Hv with 3 wt.% CNTs, and 933 Hv with 5 wt.% CNTs in thermally sprayed YSZ. The results obtained are highly appreciable when compared to the hardness (454 Hv) of thermally sprayed pure YSZ coating. From results of wear tests, it was found that at slow speed (i.e., 319 rpm), the minimum mass loss was identified for all the three different combinations of CNTs reinforced coatings. However, 5 wt.% of CNTs in YSZ has very minimum wear at 5 kgf load and subsequently mass loss increased with the decrease in CNTs weight percentage proportion. Based on wear resistance, it was found that the 5 wt.% CNTs in YSZ has a maximum wear resistance. Severe wear scars and coating delamination in 1% CNTs reinforced coatings were identified from the microstructural analysis. Therefore, addition of CNTs in YSZ coatings has a significant impact over the wear resistance and mechanical properties improvement of the coatings.